Advanced exergetic analysis of a refrigeration system for liquefaction of natural gas - Morosuk, Tatiana; Mohd Nazri, Omar; Tsatsaronis, George; Naw, Rolanda (Industrial Energy Systems Laboratory (LENI), 2013)
International Conference on Efficiency, Cost, Optimization, Simulation and Environmental Impact of Energy Systems (ECOS) 2010, 14th - 17th June 2010 organized by Industrial Energy Systems Laboratory (LENI) at Lausanne, Switzerland.